Basaloid Squamous Cell Carcinoma: An Unusual Ball-Valve Laryngeal Obstruction - Tan, Sien Hui (Iran J Otorhinolaryngol, 2015)
INTRODUCTION: A rare case of basaloid squamous cell carcinoma (BSCC) of the larynx, which has not been previously reported, is described. CASE REPORT: A 60-year-old man was presented to the Otolaryngology Department with progressive dyspnoea and dysphagia to solids for over a period of 1 week. Direct laryngoscopy revealed a tumour at the laryngeal aspect of the epiglottis, which prolapsed into the laryngeal inlet each time the patient inspired. This resulted in an inspiratory stridor despite adequate glottic opening and normal mobility of the vocal cords. CONCLUSION: Therefore, in cases where a ball-valve lesion causes intermittent life-threatening airway obstruction, BSCC of the larynx, though rare, must be considered as a differential diagnosis.